Evaluation of improved potato cultivars according to their agronomic traits under the conditions of Murmansk Province - T. E. Zhigadlo (Труды по прикладной ботанике, генетике и селекции)
Background. The main objective of the Polar Experiment Station is to maintain and preserve the global potato collection of VIR. The collection is replenished with new improved potato cultivars. Their main agronomic traits are studied: earliness, productivity, starch content in tubers, resistance to viruses and fungi, etc. After three years of evaluation, cultivars are transferred to the maintenance collection.Materials and methods. Thirteen new potato accessions the from VIR collection were studied in 2018–2020 for valuable agronomic traits under the extreme conditions of Murmansk Province using VIR’s guidelines.Results and conclusions. The study made it possible to characterize this set of accessions according to their phenological parameters, earliness, productivity, and disease resistance. Accessions that exceeded the reference (‘Khibinskiy ranniy’, k-6928) in a number of indicators were identified. Three accessions demonstrated the best productivity across the years of the study: k-25327 (local from Georgia), k-25330 (‘KazSIP’) and k-25314 (‘Arizona’). Accession k-25311 (‘Gornyak’) was selected for earliness, productivity, and marketability of tubers; k-25302 (‘Babayev’) was identified for its productivity and high marketability of tubers; k-25302 (Arrow’) showed high productivity, high marketability of tubers, and large tuber size. The accessions selected for their starch content were k-25330 (‘KazSIP’) and k-25327 (local from Georgia). Six potato accessions were not affected by fungal diseases: k-25258 (‘Sunkar’), k-25302 (‘Babayev’), k-25311 (‘Gornyak’), k-25314 (‘Arizona’), k-25339 (‘Bravo’) and k-25317 (‘B-O-E’). Symptoms of viral diseases were not found in k-25311 (‘Gornyak’), k-25321 (‘Labadia’), k-25327 (local from Georgia), k-25336 (‘Ametist’) and k-25318 (‘Cogu Valley’). The results of the study made it possible to recommend them for new potato breeding programs in Murmansk Province.